Public attitudes to potential synthetic cells applications: Pragmatic support and ethical acceptance. - Olga Rook; Hub Zwart; Marileen Dogterom (PLoS ONE)
Synthetic cells constructed bottom-up represent a novel direction in Synthetic Biology. It has the potential to deepen the scientific understanding of life and, in the longer run, to open up new pathways for medical and environmental applications. Mapping preliminary public attitudes towards emerging technologies is an important step to further societal discussion and stakeholder participation. We conducted a vignette survey with nationally representative samples from 13 European countries (Czech Republic, France, Germany, Greece, Hungary, Italy, the Netherlands, Poland, Romania, Spain, Sweden, Turkey, and UK; N =  8,382) to explore public attitudes towards prospective synthetic cell technologies, such as anticancer therapy, CO2 emissions conversion to biofuel, and industrial waste recycling. Using data-driven techniques, we built a decision tree model of the factors affecting participants' attitudes and summarized the prevalent themes behind one's motivation. Our findings suggest substantial public support for prospective synthetic cell applications in the societally beneficial fields, most notably in healthcare.